The professional profile of the school librarian in Aragon: a case study in Aragonese school libraries - Puente Cadena, Isabel (Revista General de Información y Documentación, 2024)
The professional profile of the person in charge of the school library in Aragon is described and analyzed, focusing on non-university teaching centers in this autonomous community. Aspects such as determining the functions and activities that this professional person carries out, as well as the time dedicated to the school library, are studied; discover if educational centers have a library commission and support teams that collaborate in the organization and management of the school library; find out the basic and/or specific training of the people in charge of the school library; know the procedure and assignment criteria used to assign the role of person responsible for the school library, and check the degree of compliance with existing guidelines and recommendations. To achieve these objectives, a questionnaire has been designed and prepared and sent to non-university teaching centers in the Autonomous Community of Aragon, and thus know the professional performance of the people in charge of school libraries. In Aragón, at present, it cannot be said that the library is in the hands of a school librarian, since the people who serve them are teachers who, in most cases, do not have the required training or professional qualifications, nor the Jobs are adequately defined by educational administrations, so this situation has a negative impact on the functioning of school libraries and the services they offer.